Cycle of Segregation : Social Processes and Residential Stratification - Krysan, Maria; Crowder, Kyle (Book collections on Project MUSE., 2017)
The Fair Housing Act of 1968 outlawed housing discrimination by race and provided an important tool for dismantling legal segregation. But almost 50 years later, residential segregation remains virtually unchanged in many metropolitan areas, particularly where large groups of racial and ethnic minorities live. Why does segregation persist at such high rates and what makes it so difficult to combat? In Cycle of Segregation, sociologists Maria Krysan and Kyle Crowder examine how everyday social processes shape residential stratification. Past neighborhood experiences, social networks, and daily activities all affect the mobility patterns of different racial groups in ways that have cemented segregation as a self-perpetuating cycle of the twenty-first century. Because historical segregation has shaped so many of these experience, even seemingly race-neutral decisions about where to live can reinforce residential stratification. To overcome this cycle, Krysan and Crowder advocate multilevel policy solutions that pair inclusionary zoning and affordable housing with education and public relations campaigns that emphasize neighborhood diversity and high-opportunity areas. Cycle of Segregation demonstrates why a nuanced understanding of everyday social processes is critical for interrupting entrenched patterns of residential segregation--back cover.